Measuring the roles and essential characteristics of professional educator in UiTM Melaka (City Campus and Lendu Branch) - Haris, Siti Melinda; Adenan, Amie Azreen (2008)
Ensuring the quality of professional educator is important in this new era. The goal of an educator is to inspire students toward excellence while promoting learning as a lifelong process. The educator has the responsibility of teaching this nation's greatest natural resource. Educators should achieve the standard characteristics of professional educator and play their role effectively. This research focuses on the measuring the perception on the roles and level of essential characteristics among the professional educators. This research was carried out both in UiTM Kampus Lendu and Kampus Bandaraya Melaka from 12 February 2008 and was collected on 18 February 2008. 69 respondents were participating and cooperate in answering the questionnaires distributed to them. The findings of this study concluded that the perception on role of professional educator is at 4.1232 which can be considered as high. Level of characteristics of professional educator is at the moderately high level with total mean value of 4.0364. It is found that there is positive and low relationship between the perception of role and level of characteristics of lecturers which means that at a higher level of characteristics, the perception of role is also at higher level. However, only working years are significant to the role of professional educators.